A Case of Severe, Silent Fetomaternal Haemorrhage (FMH) Detected by Mixed-Field in the Mother's ABO Typing - Aurora Espinosa; Kristin Finserås; Grete Storvold; Tone Wedø; Kristin Fonn; Seema Mathew; Eline B Seljeflot; Eszter Vanky (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2016)
Introduction: Fetomaternal haemorrhage (FMH) refers to the passage of fetal erythrocytes to the maternal circulation. In most pregnancies, small amounts of fetal erythrocytes can cross over to the maternal circulation without causing problems for the fetus. In rare occasions, the FMH can result in fetal anaemia or in fetal death.  Case report: Here, we present a case where a 30-year-old, II gravida, I para, in gestational week 35 reported decreased fetal movements, leading to the diagnosis of severe FMH. The fetal haemorrhage calculated by Kleihauer-Betke test was estimated to 287 mL, causing a mixed-field in the mother's ABO typing, as the mother and the baby had different blood types. Fetal anaemia was suspected and diagnosed by Doppler ultrasound, and emergency caesarean section was performed, saving the baby's life.  Discussion: Severe FMH is very rare, and may present as decreased fetal movements, together with sinusoidal fetal heart rate pattern. This condition requires rapid intervention such as intrauterine transfusions or emergency caesarean section. Assessment of fetal anaemia by Doppler ultrasound should be considered in mothers reporting decreased fetal movements.